CHILDREN PROTECTION AGAINST SEXUAL EXPLOITATION THROUGH SIRI MARRIAGE: AN INDONESIAN EXPERIENCE - Fitri, Winda (Tadulako University, 2021)
The problem that develops in the community regarding children is the exploitation of children. This action is considered an act that has violated legal norms, because it has taken away the inherent rights of the child. Child exploitation is an arbitrary act and discriminatory treatment against children by the community or family to force the child to do something without paying attention to children's rights, such as their physical and mental development. The practice of exploiting children, especially sexual exploitation, has been carried out in various ways, one of which is siri marriage. Siri marriage is a new mode to legalize the crime of sexual exploitation of children. Based on Islamic law, unregistered marriage is a legal marriage, because the unregistered marriage has met predetermined marriage validity criteria. However, unregistered marriage will be a criminal offense if it is committed against a child with the motive of legalizing sexual relations. Normatively, Indonesia applies preventive and repressive measures. As a preventive measure, Indonesia has enacted a series of laws regulating prohibitions, sanctions, and protection measures that must be provided to child victims of sexual exploitation. In addition, a form of repressive protection is carried out by providing a deterrent effect through sanctions on parents or other parties who deliberately allow and use it to gain benefits in child marriage through unregistered marriage which can be categorized as a criminal act, therefore in the perspective of criminal law it can be put together. punishment to parents who have been involved in the act of marrying off their children at an early age so that the imposition of criminal sanctions can provide legal certainty.